On memoir literature in the years 1941 to 1956 - Heltserienė, S. (Literatūra, 1969)
From 1941 to 1956 in the USSR appeared more than six hundred editions (editio princeps and later editions) in the genre of memoiristics: diaries, books containing personal letters, rememberings of the participants of the Great Patriotic War. These editions are still insufficiently studied by literary criticists. May be therefore they are underestimated by some scholars, who, wanting to determine the place of war-memoiristics in the process of literary creation, are generally operating only with the books that appeared between the years 1956 to 1966. On this time the highly popular of the last decade editions of war-memoirs in the USSR can not be fully understood without connection with the books of the corresponding genre, that appeared from the very beginning of the Great Patriotic War till 1956. The author in the present article tries to deal more completely, than it was formerly done in literary criticism with the reconstruction of the origin of memoiristics as a whole and their further revival at wartime and the post-war years. Special attention is paid on the printing of the works, with the emphasising and explaining of various tendencies in the field of the edition of memoir works, depending from various historical events.